Retos en el diseño curricular de un programa de inglés para adultos - Echeverri-Sucerquia, Paula Andrea; Quinchia Monroy, Mabel Cristina (Colombian Applied Linguistics Journal, 2016)
In this article we describe the experience of a group of English teachers in charge of the curriculum renewal of an English program for adults. With the purpose of creating a relevant curriculum, the designers drew on principles for, a practical curriculum, the critical curriculum, and the participatory curriculum. Results from this experience suggest that in order for a language program to be effective, its curriculum should be relevant; that is, the curriculum should take into account the needs and interests of adult students. Second, the curriculum proposal should have a clear theoretical and methodological conceptualization that supports the processes that take place within the program. Third, the curriculum proposal should put forth tasks that resemble activities that adults carry out in their daily lives. Fourth, the implementation of the curriculum proposal should be supported by a teacher development and mentoring program. Lastly, we argue that in order to achieve a relevant curriculum, it is necessary to have the financial and logistics support from the program administration, as well as the teachers’ commitment and positive attitude towards change.